The relationship between ICT adoption and business performance in Malaysia and Indonesia - Ong, S. Y. Y.; N. F. Habidin; M. I. Salleh; N. M. Fuzi (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper reviews the relationship of information communication technology adoption (ICT) and Business Performance (BP) from women entrepreneur perspective in Malaysia and Indonesia. The aim of this paper is to identify the dimension of ICT adoption and BP to develop a conceptual framework for further study about the relationship to identify those that can determine women entrepreneur success. To achieve this objective, literature review is conducted by extend number of literature in ICT, BP, and women entrepreneur. Related studies are review and analyze by using literature table. The finding of this paper reveals a proposed conceptual framework and hypothesis that gain support from literature. The significant of this study is expected to provide guideline for women entrepreneurs in Malaysia and Indonesia who wish to adopt ICT in their business and help them to evaluate the relationship with BP. This study can assist women entrepreneurs in considering the adoption of Electronic commerce (EC) and Mobile commerce (MC) to embark themselves in technology and innovation. Further efforts are to test this conceptual framework and hypothesis by using Structural Equation Modelling (SEM) to develop a research model.